Foundations of human resource development - Swanson, Richard A.; Holton, Elwood F. (San Francisco : Berrett-Koehler, 2001)
The book is a comprehensive guide providing an up-to-date overview of the state of the profession as well as the terminology and processes required for sound Human Resource Development (HRD) practice and study.
Includes index.
Includes bibliographical references (p. 387-419).
rua 30/05/17
Loans.
Keywords: Employees; Personnel management; Manpower planning; Human capital